The Phenomenon of Husbands Living with Their Wives: A Muslim Family Economic Perspective - Al-Mu'min, A Khaerul (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2023)
This research aims to analyze the public's view of the husband who rides to his wife. Researchers use qualitative phenomenological methods. The research was conducted for 3 months. The research method uses secondary data derived from previous research, while the researcher obtained primary data from interviews with two families in Kosambi and Cilampek. Based on the results of this research, researchers found that this phenomenon started with a public figure whose wife became the backbone of the family, which had an impact on society, so that many working wives said that their husbands were living. There are three categories of husbands in building the family economy with the help of their wives, namely firstly the husband's income is the same as the wife's, secondly the husband's income is less than the wife's and thirdly the husband who does not work then asks his wife for her husband's needs. An indicator of a husband who lives a life is a husband who doesn't think about providing for the family at all, while the wife is the backbone of the family. As long as the husband is still working, even though his income is the same or less than the wife's income, the wife must still respect her husband Penelitian ini bertujuan unutuk menganalisis pandangan masyarakat tentang suami menumpang hidup kepada sang istri. Peneliti menggunakan metode kualitatif fenomenologi. Penelitian dilakukan selama 3 bulan. Metode penelitian menggunkan data sekunder berasal dari penelitian-penelitan sebelumnya, sedangkan data primer peneliti dapatkan dari wawancara dua keluarga di Kosambi dan Cilampek. Berdasarkan hasil dari penelitan ini, peneliti menemukan bahwa fenomena ini berawal dari seorang publik figur istri menjadi tulang punggung keluarga, yang berdampak pada masyarakat, sehingga banyak istri bekerja mengatakan bahwa suaminya menumpang hidup. Ada tiga katagori suami dalam membangung ekonomi keluarga dibantu istri, yaitu pertama pendapatan suami sama dengan istri, kedua pendapatan suami lebih kecil dari istri dan ketiga suami yang tidak bekerja kemudian meminta kebutuhan suami kepada istrinya. Indikator suami yang menumpang hidup adalah suami yang sama sekali tidak memikirkan nafkah keluarga, sedangkan istri menjadi tulang punggung keluarga. Selama suami masih bekerja meskipun nafkahnya sama atau lebih kecil dari penghasilan istri, maka istri harus tetap menghormati suaminya